Role of AI in Predicting and Mitigating Threats: A Comprehensive Review - Aftab Arif; Ali Raza A Khan; Muhammad Ismaeel Khan (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
The field of danger prediction and mitigation is changing due to artificial intelligence (AI) in a number of areas, including national security, cybersecurity, public health, and finance. This paper examines how artificial intelligence (AI) might improve threat detection, response, and prevention. It emphasizes AI's capacity to scan large datasets and spot patterns that speed up decision-making. Anomaly detection in cybersecurity, disease outbreak and natural disaster prediction using predictive modeling, and financial system fraud detection are some of the key uses. The application of AI technologies, however, brings up important ethical issues, such as algorithmic bias, data privacy, responsibility, and the requirement for openness. In order to responsibly manage AI implementation, the essay highlights the significance of ethical AI practices and the creation of strong regulatory frameworks. Future trends point to a move toward more sophisticated machine learning methods, the incorporation of AI with cutting-edge platforms like block chain and the Internet of Things (IoT), and an emphasis on human-AI cooperation. The article's conclusion is that, despite AI's enormous potential to improve security and resilience, responsible use of this disruptive technology will need proactive interaction with a variety of stakeholders and ethical considerations. Society can successfully handle the complexities of AI and make sure it works as a positive force to counteract emerging risks by encouraging a collaborative approach.